Using porphyry ore mineralization, in combination with geochemical and geological data to understand complex tectonomagmatic origins of magmatic belts: a regional study of the Absaroka, Challis, and Lowland Creek volcanic provinces of Idaho, Montana, and Wyoming, USA - Broley, Kyle C. (Kansas State University, 2024)
A significant part of the North American Cordillera contains a discontinuous north-northwestern trending chain of Eocene volcanic centers (e.g., the Challis-Kamloops volcanic belt), intermittently spanning > 2000 km from southern Idaho and Wyoming in the northwestern United States to central British Columbia in western Canada. The core area of this study is southern end of the Challis-Kamloops volcanic belt, specifically the Absaroka, central Idaho Challis, and Lowland Creek volcanic provinces of the central North American Cordillera. This study shows that a combination of regional differences in porphyry mineral systems (e.g., Cu- vs. Mo dominated), combined with volcanic types and bulk rock geochemistry of igneous rocks, can be used to help decipher complex tectonomagmatic origins. Comparative Sr/Y versus wt% SiO₂ and (Eu/Eu*)/Yb data (e.g., mean Sr/Y = 77.1), coupled with Cu-porphyry deposits associated with a 230-km-long belt of stratovolcanoes, supports an arc origin for the Absaroka volcanic province. The central Idaho Challis volcanic province has chemical indices not conducive to Cu-porphyry mineralization (e.g., mean Sr/Y = 24.0), which, coupled with the presence of Mo-porphyry mineralization and a lack of stratovolcanoes, supports an extensional tectonomagmatic origin. Together, the disparate types of porphyry ore deposits, geochemical, and geologic data is used to create a new regional tectonic model to for the origins of the Absaroka, central Idaho Challis, and Lowland Creek volcanic provinces that involves the uneven subduction, tearing, and eventual foundering of the Farallon plate between 55 – 45 Ma.
Keywords: Porphyry Cu; Porphyry Mo; Challis volcanic province; Absaroka volcanic province; Lowland Creek volcanic province; Tectonomagmatic